PET evidence of preclinical cerebellar amyloid plaque deposition in autosomal dominant Alzheimer's disease: Neuroimaging / imaging and genetics. (7th December 2020) - Ghisays, Valentina; Lopera, Francisco; Goradia, Dhruman D.; Protas, Hillary D.; Malek‐Ahmadi, Michael H.; Chen, Yinghua; Devadas, Vivek; Luo, Ji; Lee, Wendy; Brown, Christopher T.; Baena, Ana; Bocanegra, Yamile; et al.
Abstract: Background: In contrast to late onset Alzheimer's disease (LOAD), the late clinical stages of autosomal dominant Alzheimer's disease (ADAD) are associated with greater neuropathological evidence of cerebellar amyloid plaque (Aß) deposition. In this study, we used PET measurements of fibrillar Aß burden to characterize the presence and age at onset of cerebellar Aß deposition in cognitively unimpaired Presenilin‐1 (PSEN1) E280A mutation carriers from the world's largest extended family with ADAD. Method: Florbetapir and PiB PET data from two independent studies – API ADAD Colombia Trial (NCT01998841) and the Colombia‐Boston (COLBOS) longitudinal biomarker study were included. Template‐based cerebellar standard uptake value ratios (SUVR), using a known‐to‐be‐spared pontine reference region, were used to 1) compare 290 cognitively unimpaired 28‐56 year‐old mutation carriers and non‐carriers; 2) characterize associations among cerebellar‐to‐pontine SUVR and age, mean cortical SUVRs, and episodic memory performance; and 3) estimate the age at which cerebellar‐to‐pontine SUVRs begins to differ significantly in the carrier and non‐carrier groups. Result: Compared to non‐carriers, cognitively unimpaired carriers had higher cerebellar‐to‐pontine florbetapir and PiB SUVRs ( p <.0001). Mean cortical SUVRs were positively correlated with age and negatively correlated with episodic memory performance ( p <.05). SUVRs began to distinguish carriers from non‐carriers at age 34, 10 years before the carriers' estimated age at mild cognitive impairment onset. Conclusion: This PET study provides evidence of cerebellar Aß plaque deposition in cognitively unimpaired mutation carriers starting years before their clinical onset. Additional studies are needed to clarify the impact of using a cerebellar versus pontine reference region on the power to detect and track ADAD progression, even in preclinical stages of this disorder.